Pembuatan Iklan Animasi 2D untuk Produk Minuman Isotonik Sebagai Media Promosi Menggunakan Adobe Animate - Shodik Permana; Muhammad Sulthon Abdillah; Ina Sholihah Widiati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
In the fast-paced modern era, competition in the food and beverage industry has intensified. Consumers are often confused to choose because of the many brands available. Promotional media is important to convey product information effectively. 2D animation emerges as a great choice because it is able to attract attention with creative and memorable visuals. By using dynamic characters and bright colours, 2D animated ads can target a wide range of audiences and demonstrate the use of products in everyday life. The main goal is to build brand awareness and encourage consumers to try the product. This research will create a 2D animated advertisement for an isotonic drink using Adobe Animate, designed to be persuasive and leave a deep impression on the audience. The flow of making this animated advertisement starts from the Pre-production stage, the Production stage and the Post-production stage, by making this advertisement, the delivery of information from a product will become more creative and not monotonous, so that it can be watched by consumers who can get information.